Progress on Multi-Dimensional Structural Design of Nano-Silicon Anodes for Lithium Ion Batteries - Belyonova, Aleksandra A.; Fleis, Maria (Journal of Functional Materials and Applied Engineering, 2022)
Silicon-based anode materials are considered highly promising candidates for next-generation lithium-ion battery systems, owing to their high theoretical capacity, relatively low operating potential, and abundant natural reserves. However, their practical commercialization is significantly hindered by intrinsic material limitations, including severe volumetric expansion during lithiation, poor electronic conductivity, and the formation of unstable solid electrolyte interphase (SEI) layers. These collective deficiencies result in compromised cycling durability. This review initially examines the fundamental mechanisms governing volume expansion and SEI film evolution in silicon anodes, subsequently providing comprehensive analysis of the underlying expansion phenomena. The dual failure modes (mechanical and chemical instability) were analyzed, while the detrimental consequences of cycling degradation were expounded. The modification research on silicon-based anodes in recent years was elaborated from the perspective of multi-dimensional nano-silicon structure design, including the design, preparation, advantages and disadvantages of 0D (silicon nanoparticles, silicon quantum dots, etc.), 1D (silicon nanowires and silicon nanotubes), 2D (silicon nanosheets, silicene), and 3D (porous silicon, silicon nanosponges) nano-silicon materials, as well as the differences in structure, performance and application of other silicon-based anode materials (pure Si anode, SiOₓ anodes, Si/C composite anodes). Finally, the critical requirements for advancing novel technological innovation, deepening mechanistic fundamental insights, developing in-situ characterization techniques, and implementing synergistic modification strategies were emphasized. Future research directions and application prospects for high-performance silicon-based anode materials were subsequently outlined.